Formulation and Evaluation of Multiple Unit Floating Beads of Antiulcer Drug - Chandra, Dr. Amrish (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The present study was focused on the development of a multiple unit floating (gastroretentive) beads of lafutidine for prolongation of the gastric retention time and increase in absolute bioavailability with enhanced patient compliance in the treatment of peptic ulcer. Materials and Methods: Floating beads of lafutidine were prepared using ionotropic gelation method using hydrophilic polymer (hydroxypropyl methylcellulose [HPMC K4M]), gas-forming agents (calcium carbonate), gelling agent (sodium alginate), and crosslinking agent (calcium chloride). 23 full factorial designs were applied to optimize the developed formulation. All the formulated beads were subjected to various evaluation parameters such as micromeritics properties, percentage drug entrapment, percentage swelling index, percentage buoyancy, and in vitro drug release studies. Calcium chloride, HPMC K4M, and Calcium carbonate were selected as independent variables at two different levels. t80% was selected as the response variable. Scanning electron microscope (SEM) study was carried out on the optimized formulation. Results and Discussion: The optimized formulation remains buoyant for more than 12 h. The in vitro drug release results indicated that increasing the concentration of HPMC K4M resulted in sustained effect with long floating duration. LF7 was selected as the optimized formulation. In vitro release profile of optimized formulations followed Higuchi model with non-Fickian (anomalous) diffusion. SEM studies showed their spherical shape with perforated smooth surface and cavity inside beads. Conclusion: Lafutidine-loaded floating beads were successfully prepared and prove to be useful for the prolonged gastric residence of the drug, better bioavailability, and patient compliance for enhanced anti-ulcer activity.